PENGARUH BRAND AMBASSADOR DAN HALLYU TERHADAP KEPUTUSAN KONSUMEN MELAKUKAN BRAND SWITCHING DAN IMPLIKASINYA TERHADAP KEPUASAN KONSUMEN KOSMETIK DI JAKARTA - R, Mila Febrina (Universitasdiwangsa Jambi, 2019)
Purchase decisions to brand switching is a stage where consumers recognize their needs first by looking for information, then evaluate, make purchases, and then perform post-purchase evaluation. Several factors that influence consumer decisions to brand switch are brand ambassador and hallyu influence. Brand ambassadors are cultural icons, in which they act as marketers? tools often identical or related to celebrities or public figures. Hallyu is a phenomenon of the Korean Culture rapid growth through mass media. The sample in this study is consumers who previously had used cosmetics from other countries and have used Korean cosmetics in 10 malls Jakarta area, amounting to ninety-nine respondents, calculated by Slovin method. The type of data used is the primary data through questionnaires. Data analysis method used is multiple linear regression analysis using SPSS, which previously tested with classical assumption. The dependent variable used in this study is consumer decision to brand switch and also consumer satisfaction, while the independent variable is brand ambassador and hallyu influence. The results showed that simultaneously and partially brand ambassador and hallyu has significant positive effect on consumer decisions to brand switching. Variable consumer decision to do brand switching have a positive effect significantly to customer satisfaction.